Generation of functional scFv intrabody to abate the expression of CD147 surface molecule of 293A cells - Tragoolpua K. (2014)
Background: Expression of intracellular antibodies (intrabodies) has become a broadly applicable technology for generation of phenotypic knockouts in vivo. The method uses surface depletion of cellular membrane proteins to examine their biological function. In this study, we used this strategy to block the transport of cell surface molecule CD147 to the cell membrane. Phage display technology was introduced to generate the functional antibody fragment to CD147, and we subsequently constructed a CD147-specific scFv that was expressed intracellularly and retained in the endoplasmic reticulum by adenoviral gene transfer. Results: The recombinant antibody fragments, Fab and scFv, of the murine monoclonal antibody (clone M6-1B9) reacted specifically to CD147 by indirect enzyme-linked immunosorbent assays (ELISA) using a recombinant CD147-BCCP as a target. This indicated that the Fab- and scFv-M6-1B9 displaying on phage surfaces were correctly folded and functionally active. We subsequently constructed a CD147-specific scFv, scFv-M6-1B9-intrabody, in 293A cells. The expression of CD147 on 293A cell surface was monitored at 36 h after transduction by flow cytometry and demonstrated remarkable reduction. Colocalization of scFv-M6-1B9 intrabody with CD147 in the ER network was depicted using a 3D deconvolution microscopy system. Conclusion: The results suggest that our approach can generate antibody fragments suitable for decreasing the expression of CD147 on 293A cells. This study represents a step toward understanding the role of the cell surface protein, CD147. © 2008 Tragoolpua et al; licensee BioMed Central Ltd.